Produtos naturais marinhos indutores de morte celular imunogênica em melanoma - Brito, Thaís Lima de (2023)
Melanoma metastatic is a low-incidence tumor, although with high lethality. Despite the advances obtained with target therapy and immunotherapy, the five-year survival rate is only 35%. Considering that most patients have an unfavorable prognosis, the search for new drugs or new therapeutic strategies is necessary. Some classic cytotoxic chemotherapeutic agents such as doxorubicin and paclitaxel induce immunogenic cell death (ICD). Tumor cells undergoing MCI release damage-associated signals (DAMPs), which activate an antitumor immune response. In this way, MCI inducers produce more effective and lasting responses due to the elimination of tumor cells directly by cytotoxicity and the immune system. Thus, prospecting candidate compounds for chemotherapeutic drugs that induce ICD is a strategy that aims to increase the expectation of translation in the drug development process. Marine natural products are a very promising source of cytotoxic compounds. Tartrolon D/E (TRL) and chromomycin A5 (CA5) molecules are marine natural products synthesized by microorganisms of the genus Terednibacter sp. and Streptomyces sp., respectively. The present work aimed to study the antitumor potential of TRL and CA5 in human melanoma, as well as the antitumor effect in murine melanoma and the toxicity of CA5. Chapter 1 describes the studies carried out with the aim of evaluating the induction of ICD by TRL in human metastatic melanoma cells. Initially, the sulforhodamine B (SRB) assay was performed to evaluate the effect of the compound on cell proliferation. Then, the induction of stress, autophagy and cell death, as well as the release of DAMPs, and the expression of surface markers by flow cytometry and immunoblot were evaluated. Furthermore, the probable targets of tartrolon D were predicted using the target fishing strategy. TRL showed antiproliferative activity in 7 tumor cell lines (HCT 116, B16-F10, WM293A, SK-MEL-28, PC-3M and MCF-7) and two non-tumor cell lines (HEK293A and L929), with inhibitory concentration value average of 0.04 uM to 13 uM after 48 hours of incubation. The following studies were performed with B16-F10, WM293A and SK-MEL-28 melanoma cell lines. TRL induced regulated cell death, reticulum stress, and autophagy in the evaluated cells. Furthermore, TRL also induced the release of DAMPs typical of MCI, namely nuclear HMGB1 release, and the externalization of ERp57, calreticulin and HSP70 in the plasmatic membrane. Additionally, there was an increase in the expression of surface markers MHC II and CD1d in B16-F10 cells incubated with TRL. This complex phenotype of stress and cell death associated with the release of DAMPs in cells exposed to TRL is typical of ICD. Chapter 2 aimed to evaluate the translational potential of CA5, previously identified as a genuine inducer of MCI, through the evaluation of its antitumor effect and toxicity in a murine melanoma model. In vivo assays (C57BL/6 females, CEUA No 7270010621) to identify tolerated dose demonstrated that 1 mg/kg of CA5 induces severe pain and discomfort in animals. Additionally, mice transplanted with B16-F10 cells were treated with three different chemotherapy strategies: metronomic, maximum tolerated dose and intermittent average dose. Animals treated with 0.3 mg/kg CA5 3 times every 72 h (intermittent medium dose approach) exhibited a 60% reduction in tumor volume. However, these animals showed signs of pain, discomfort, lesions in the peritoneum region, in addition to other alterations in the peritoneal cavity indicative of toxic effects. The CA5 group also had leukopenia, mainly related to the reduction of lymphocytes. However, there were no alterations in the biochemical parameters evaluated, such as ALT, creatinine and urea. Thus, it is concluded that the TRL and CA5 compounds cause changes typical of ICD and are promising candidates for chemotherapy for the treatment of metastatic melanoma and, therefore, deserve further studies of preclinical development.